2022
DOI: 10.1098/rspb.2022.0980
|View full text |Cite
|
Sign up to set email alerts
|

Predator responses to prey camouflage strategies: a meta-analysis

Abstract: Although numerous studies about camouflage have been conducted in the last few decades, there is still a significant gap in our knowledge about the magnitude of protective value of different camouflage strategies in prey detection and survival. Furthermore, the functional significance of several camouflage strategies remains controversial. Here we carried out a comprehensive meta-analysis including comparisons of different camouflage strategies as well as predator and prey types, considering two response varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Here, positive effect size values represent lower populations of pests and higher crop yield with the presence of predators. To facilitate the interpretation of the results, we back-transformed the lnR values [(exp lnR −1)]×100, to obtain the differences between treatment and control in percentages (see [59], for example).…”
Section: Methodsmentioning
confidence: 99%
“…Here, positive effect size values represent lower populations of pests and higher crop yield with the presence of predators. To facilitate the interpretation of the results, we back-transformed the lnR values [(exp lnR −1)]×100, to obtain the differences between treatment and control in percentages (see [59], for example).…”
Section: Methodsmentioning
confidence: 99%
“…de Alcantara Viana et al . [ 1 ] examine the efficiency of different camouflage strategies by conducting a thorough meta-analysis. They compare predator search time and attack rate among five different camouflage strategies, three predators and three prey types, showing that both camouflage strategy and prey type can influence effectiveness.…”
mentioning
confidence: 99%
“…de Alcantara Viana et al . [ 1 ] provide support for these differing benefits and costs, demonstrating that strategies that prevent prey detection (background matching, disruptive coloration) or prey recognition (masquerade) increase predator search time, whereas strategies that deflect attack or reduce accuracy (eyespots, motion dazzle) do not impact search time. They also found that the three strategies that reduce attack rate—background matching, disruptive coloration and motion dazzle—cause a reduction of similar magnitude.…”
mentioning
confidence: 99%
See 2 more Smart Citations